Structured cyclic peptide mimics by chemical ligation. Issue 5 (23rd March 2022) - Atkinson, Bethany C.; Thomson, Andrew R.
Abstract: We report the development of a β‐turn mimic that allows the direct formation of cyclic peptides through a spontaneous cyclisation under standard solid phase peptide synthesis (SPPS) cleavage conditions. The mimic is formed via an acylhydrazone, which is either reduced in situ by triisopropylsilane‐trifluoroacetic acid, or which can be isolated and reduced in a separate step. This method uses commercially available reagents and is compatible with manual and automated SPPS methods. The cyclisation is tolerant of polar residues at the C ‐terminal position, with the exception of asparagine, for which a subsequent structural rearrangement similar to aspartimide formation was observed. The cyclisation method has been shown to tolerate ring sizes equivalent to 5–10 amino acid residues. We have used this method to design and synthesise potential selective integrin binding sequences with controlled conformations. Abstract :